On the efficiency of combined ion implantation for the creation of near‐surface nitrogen‐vacancy centers in diamond. Issue 8 (18th July 2016) - Fávaro de Oliveira, Felipe; Momenzadeh, Seyed Ali; Antonov, Denis; Fedder, Helmut; Denisenko, Andrej; Wrachtrup, Jörg
Abstract: The efficiency of co‐implantation of different ion species to generate near‐surface nitrogen‐vacancy (NV) centers in diamond is analyzed by comparing the areal densities of NV centers corresponding to various experimental conditions. In particular, the effect of helium (6keV He 2 + ) and carbon (10keV C + ) co‐implantation within a wide range of ion fluences are studied. The total density of NV centers by co‐implantation are shown to be basically a sum of the nitrogen‐induced NV centers and those activated from residual nitrogen impurities present in the substrate (approximately 1ppb) by the excess of vacancies at the carbon‐ and helium‐induced ion tracks. Such low efficiency of the co‐implantation events is discussed considering the model of local clusters of vacancies at each implantation‐induced ion track. This is also experimentally supported by the presence of a photoluminescence (PL) background related to radiation‐induced defects measured within all implanted areas with high carbon and helium ion fluences. Further limits set by the annealing temperature are also discussed.